2016
DOI: 10.1016/j.matdes.2016.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of GP(I) zone formation during quench in an industrial AA7449 75 mm thick plate

Abstract: The GP(I) zone formation during quench is simulated in an industrial Aluminum alloy AA7449 75 mm thick plate by using a multi-class precipitation model. For this purpose, results of in situ SAXS experiments are reported. A methodology is presented that takes advantage of the collected data to derive i -a thermodynamic description for GP(I) zones from reversion heat treatments by using a solubility product and ii -the influence of excess vacancies on diffusion coefficients. This approach allows reproducing reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…In addition, the electrical conductivity is decreased upon heating too, as shown in Figure 4b. These findings indicate that the accumulated as-quenched hardeners (clusters) may dissolve upon heating because the structural stability of clusters are far less than those of large precipitates, as mentioned by the in situ SAXS results [11]. The mechanism of residual stress production has been well recognized in previous research, which is considered to be the result of inhomogeneous elastoplastic deformation due to the thermal stress during quenching [15][16][17].…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition, the electrical conductivity is decreased upon heating too, as shown in Figure 4b. These findings indicate that the accumulated as-quenched hardeners (clusters) may dissolve upon heating because the structural stability of clusters are far less than those of large precipitates, as mentioned by the in situ SAXS results [11]. The mechanism of residual stress production has been well recognized in previous research, which is considered to be the result of inhomogeneous elastoplastic deformation due to the thermal stress during quenching [15][16][17].…”
Section: Resultsmentioning
confidence: 64%
“…In a more recent study, the in situ small-angle X-ray scattering (SAXS) measurements demonstrated that the nanosized precipitates formed during quenching in an AA7449 alloy harden the material significantly, and these authors suggested that the hardeners formed during quenching are mainly solute clusters, and that other larger precipitates can be neglected [10]. It should be noted that a special phenomenon was exhibited during the experiment, wherein the volume fraction of accumulated clusters after quenching decreased significantly after reheating to temperatures between 80 to 150 • C [11]. This phenomenon can be explained as follows: The solute clusters formed in such short times during quenching that they were supercritical nucleated and were not as stable as the larger precipitates were.…”
Section: Introductionmentioning
confidence: 99%
“…The transformed volume during quenching is calculated by visualizing the quench cooling process as the superposition of a series of consecutive isothermal precipitation steps. In the analysis of hardenability and/or as-aged performance prediction, the precipitation discussed is coarse precipitation (approximately 100 nm), which occurs in an intermediate temperature range from 200-400 • C [8,9]. These coarse precipitates are ineffective hardeners, and their formation may reduce the available solute, thereby reducing the age hardening effect.…”
Section: Discussion Of Qfa Assumptionsmentioning
confidence: 99%
“…In classical QFA, the transformed volume of this coarse precipitation is linked with as-aged performance loss, and a performance loss of approximately 10-15% is generally of interest. However, in the analysis of the quench-induced hardening effect and/or the as-quenched performance prediction, the precipitation discussed is the nanosized precipitation, i.e., solute clusters, that occurs at temperatures below 200 • C [9,15,16]. Cluster hardening may result in a rapid increase in yield strength, and a performance increase beyond 10-15% is generally of interest.…”
Section: Discussion Of Qfa Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation